Authentic Happiness in the Poem Thabat Biki Al-Ayyama Wa Frahtahu by Ibrahim Naji: A Martin Seligman Perspective - Zaqhlul Ammar; Novia Fatma Azzahra; M. Anwar Mas`adi; Sulthan Naufal (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
This research aims to identify and describe the aspects of happiness in the poem “Thabat Biki Al-Ayyama Wa Frahtahu” by Ibrahim Naji based on Martin Seligman's Authentic Happiness theory. This research is a descriptive qualitative research. The data taken comes from the text of Ibrahim Naji's poems based on the positive psychology approach and were collected using a reading-and-note technique that involved intensive reading and textual analysis. The result of this research is that there are three dimensions of happiness: Pleasant Life, Good Life, and Meaningful Life, which are depicted through the struggle, love, and hope of the character “I”. The analysis found that the character “I” achieved authentic happiness through deep reflection, emotional management, and the search for the meaning of life. Although the poem appears melancholic, elements of happiness are explicitly and implicitly present, making it a complex yet positive emotional representation. This study confirms that happiness can be found through the integration of positive emotions with a deeper meaning of life, in accordance with the principles of positive psychology.